Handicraft of butterflies and moths (Insecta: Lepidoptera) in Bantimurung Nature Recreation Park and its implications on conservation - INDRA A.S.L.P. PUTRI (Biodiversitas Journal of Biological Diversity, 2016)
Putri IASLP. 2016 Handicraft of butterflies and moths (Insecta: Lepidoptera) in Bantimurung Nature Recreation Park and itsimplications on conservation. Biodiversitas 17: 823-831. The abundance of butterflies in Bantimurung Nature Recreation Park of Bantimurung-Bulusaraung National Park, South Sulawesi, Indonesia provides economic benefits to the community through butterfly’s handicrafts trading. This study aims to determine local species of commodified butterfly that are traded in various forms of craft and its implications for the conservation of butterflies. The study was conducted through the direct identification of butterfly species which are sold as crafts or deposited directly by the catchers to collectors. Data of commodified butterfly were collected using direct interviews.Data were analyzed by descriptive quantitative and qualitative. The results showed that there are 142 species of butterfly which are traded in the period of 2010-2015. The seller participants on butterfly handicrafts consist of the butterfly catchers, middlemen, craftsmen, stall employee, stall employers, and street vendors. The buyer participants consist of local tourists, tourists from outside district/province, traders from outside district/province, buyers from overseas and scientists or butterfly collectors. The butterfly price range was in between Rp. 500.00-Rp. 150,000.00/head at collectors’ level. The butterfly selling prices increased up to Rp. 7,500.00-Rp. 1,000,000.00 when they were processed into various souvenirs forms. Considering that there were so many traded butterfly souvenirs in the market, it raised an impression that there were more butterflies trapped for souvenir than free-living butterfly escaped from the trap. Commodification of butterflies needs to be regulated by setting the butterflies harvesting quota based on population in nature, sex, season and age (especially for female butterfly), accompanied by socializing rules of law, increasing public awareness about the importance of conservation butterflies, and creating new jobs for the people who depend on the butterflies trading.